Surgical problems of jejunal diverticulosis. - Geroulakos, G. (Royal College of Surgeons of England, 1987)
During a 10 year period 13 patients underwent operations for complications of jejunal diverticulosis. Two had diverticulitis, 7 perforation due to inflammation, 2 haemorrhage, 1 obstruction and 1 chronic gastrointestinal symptoms due to a large solitary diverticulum. None of the patients had a correct preoperative diagnosis. Three patients were labelled psychoneurotic because investigations prior to their emergency operation failed to reveal an organic cause for their symptoms. Small bowel contrast examinations should be included in the investigation of chronic gastrointestinal symptoms of obscure origin. Two patients on follow-up developed chronic gastrointestinal symptoms which were treated successfully with broad spectrum antibiotics.